Characterization of Tambjamines Pigment from Marine Bacterium Pseudoalteromonas sp. PM2 Indigenous from Alor Island, Indonesia - Setiyono, Edi; Adhiwibawa, Marcelinus Alfasisurya Setya; Prabowo, Matheus Randy; Brotosudarmo, Tatas H.P. (Indonesian Journal of Natural Pigments, 2021)
Pigments from marine bacteria have attracted the attention for scientists because of their extensive applications and currently exploration of new pigment sources from marine bacteria is still ongoing. Recently, we have successfully isolated six new yellow-pigmented marine bacteria, strain PS2, PM2, SB11, SB13, SB21, and SB23, isolated from seawater from different sampling sites on Alor Island, Indonesia. The UVâˆ’Vis and FTIR spectra of the crude pigment extracts of the six strains showed the characteristics of tambjamines, a group of yellow pigments commonly found in nudibranchs and bryozoans. Moreover, separation and characterization of crude tambjamines extract resulted in five different types of tambjamine with maximum absorbance at the wavelength of 374âˆ’392 nm. Based on the analysis of 16S rRNA gene sequences, strain PM2 was closely related to several species in genus Pseudoalteromonas with a similarity of more than 99%. Strain PM2 was designed as Pseudoalteromonas sp. PM2 with accession number LC505058. So far, only two marine bacteria have been known to produce tambjamine and they are from genus Pseudoalteromonas. Our new finding indicated that in the group of marine bacteria, tambjamine might be only synthesized by members from genus Pseudoalteromonas.